Sequence and phylogenetic analysis of the VP2 gene of very virulent infectious bursal disease virus isolates - Hoque, Mahfuzul M.; Omar, A.R.; Hair-Bejo, M.; Aini, I. (Taylor & Francis, 2002)
Previously we have shown that very virulent infectious bursal disease viruses (vvIBDV) that are Ssp I, Taq I and Sty I positive (92/04, 97/61 and 94/B551) but not Ssp I and Taq I positive and Sty I negative (94/273) cause high mortality, up to 80% in specific-pathogen-free chickens with significant damage of the bursal as well as nonbursal tissues. In this study, we sequenced the VP2 gene (1351 bp) of the 92/04, 94/273 and 94/B551 and compared them with other IBDV strains. All the isolates have the unique amino acid residues at positions 222A, 256I, 294I and 299S found in other vvIBDV strains. The deduced VP2 amino acids encoded by 92/04 is identical to the vvIBDV strains from Israel (IBDVKS), Japan (OKYM) and Europe (UK661), whereas the 94/273 and 94/B551 isolates have one to three amino acid substitutions. The 94/273 has two amino acid substitutions at positions 254 G to S and at 270 A to E that have not been reported before from vvIBDV strains. The 94/B551 also has one amino acid substitution at position 300 E to S, which is uncommon among other vvIBDV strains. However, phylogenetic analysis suggested that the isolates are very close to each other and all of them may have derived from the same origin as vvIBDV strains isolated from China, Japan and Europe. Even though antigenic index analysis of the 94/273 and 94/B551 indicated that the isolates are unique compared to other IBDV strains, their antigenic variation remain to be determined by monoclonal antibody study.